Pre-licensure experiences of nurses performing compulsory community service in KwaZulu-Natal, South Africa: A qualitative study. (2017) - Govender, Selverani; Brysiewicz, Petra; Bhengu, Busisiwe
Abstract: Background: Qualifying nurses from the four-year diploma or degree in nursing have to carry out compulsory community service in public health institutions before their qualifications are registered with the South African Nursing Council. Studies on nurses carrying out compulsory community service (CCS) have been reported on the stresses experienced during their CCS year but there has not been much reported on how the nurses experience their roles and responsibilities during the CCS year. Purpose: The purpose of the study was to explore pre-licensure nurses' experiences of their roles and responsibilities when carrying out CCS in KwaZulu-Natal. Methods: A qualitative approach was used to obtain data from 27 purposively selected nurses carrying out CCS in three health districts of KwaZulu-Natal through individual semi-structured interviews. Data analysis was carried out using Tesch's content analysis. Results: The main categories were: paying back the government or community, transition period for professional role, being thrown in the deep end, lack of role clarity, and frustrations with the policy. Conclusions: Although the participants did not have a clear understanding of the objectives of the CCS policy, they seem to have taken on their role as professional nurses with enthusiasm and valued the opportunity to develop professionally. Recommendations: It is recommended that nurse educators and nurse administrators provide more clarity about the CCS objectives and that there is a structured orientation programme for the nurses on their roles and responsibilities when carrying out CCS. It is also suggested that the SANC provide more clarity on the guidelines for nurses carrying out CCS.